A review of Global Carbon Markets from Kyoto to Paris and beyond: the persistent failure of implementation - Asadnabizadeh, Majid; Moe, Espen (Frontiers in Environmental Science, 2024)
This review article provides a comprehensive multidisciplinary and in-depth analysis of how the idea of Global Carbon Markets (GCM) has evolved from the Kyoto Protocol to the Paris Agreement and the post-Paris Agreement period (2015-2022) and why no real consensus has been reached after 25 years of negotiations, based on the categorisation of different arguments from different authors. We apply a semi-systematic review to 32 scientific articles, special reports, and relevant websites to analyse the failure in reaching international consensus on GCM. We apply three dichotomies, market vs. non-market-based approaches, top-down vs. bottom-up and national vs. international level. There are two striking findings. First (out of the articles that can easily be placed along all three dichotomies), there is an overwhelming majority of articles combining market-based, top-down, and international level explanations. This is however countered by a second finding, namely that there is also a clear historical trend which is unlikely to change away from top-down and towards bottom-up approaches since the Paris agreement, combined with a movement towards more non-market-based and national approaches.